METODE ANALYTICAL HIERARCHY PROCESS (AHP) DENGAN EXPERT CHOICE DALAM MENUNJANG KEPUTUSAN PEMILIHAN PERUMAHAN - Warjiyono Warjiyono (LPPM Universitas Bina Sarana Informatika, 2010)
Determining the right home choice is tricky, it is influenced by many factors, including location, price, convenience, transportation, home design and amenities. To assist in the ease of making decisions for the selection of modest housing in Cikarang, we need a method of AHP software Expert Choice 2000. Results of analysis of data collected by the respondent that is processed using the software Expert Choice 2000, was the highest criteria in selecting housing is the price that is followed by another factor,, location, transportation, comfort, models and facilities.Keywords: AHP, Expert Choice, Housing Selection Criteria